Hubungan Antara Kematangan Emosi dengan Gaya Pengambilan Keputusan karier pada Mahasiswa - Zakia Zakia Maulida (STKIP Subang, 2025)
Final-year students are at a critical stage in determining their career paths; however, many still experience difficulties in making appropriate decisions. Emotional maturity is suspected to play a role in this ability. This study aims to examine the relationship between emotional maturity and career decision-making styles among 4th–8th semester students at several public and private universities in Jakarta. The research employed a quantitative correlational method with 150 participants selected through purposive sampling. The instruments used were the Emotional Maturity Scale (EMS) to measure emotional maturity and the General Decision-Making Style (GDMS) to assess career decision-making styles.Data analysis was conducted using SPSS 26, including tests for validity, reliability, normality, linearity, heteroscedasticity, correlation, and simple linear regression. The results indicated that all instrument items were valid and reliable (Cronbach’s Alpha: EMS = 0.974; GDMS = 0.980). Regression analysis showed that emotional maturity had a significant effect on career decision-making styles (p < 0.05). The coefficient of determination (R² = 0.981) indicated that emotional maturity explained 98.1% of the variation in career decision-making styles. Correlation tests revealed a very strong and significant relationship between the two variables (r = 0.990; p = 0.000). These findings confirm that the higher the students’ emotional maturity, the better the career decisions they are able to make. This study has implications for educational institutions to develop career guidance programs that also emphasize the enhancement of emotional skills. Keywords: emotional maturity, career decision-making, students.